Influence of Age and Gender on Mental Health Help-Seeking Behavior among Mental Patients in Nyeri County: A Survey of Nyeri County Referral Hospital - publisher, publisher (African Journal of Education,Science and Technology (AJEST), 2021)
In a given year, around one in five people over the age of 18, suffer from a diagnosable mental disorder. According to World Health Organization (WHO) this condition interferes with their functionality and thus impacting their productivity in society. Considering the role played by the adult population in community development, this paper sought to establish how their functionality has lagged behind due to the mental health of this category of people in Nyeri County. The study, therefore, sought to establish the effects of age as well as gender on the mental wellbeing and help-hunting conduct of adults attending Nyeri County Referral Hospital. The study employed a cross-sectional survey design targeting the adult population. A sample size of 200 respondents was purposively selected and from whom data was collected using a General Help-Seeking Questionnaire (GHSQ) guide. The collected data was then descriptively analyzed and presented in structure of percentages, frequencies, and mean together with standard deviation. To find relationships for testing the hypothesis, chi-square tests were employed. Chi-square outcomes displayed a significant relationship [χ2 (21) = 56.976, p= 0.000, v= 0.549] between age and seeking mental health help from a friend. Similarly, there was a significant relationship [χ2 (21) = 37.530, p=0.015, v= 0.442] between age and seeking mental health help from relatives or family members. There was a significant relationship (χ2 (3) = 10.368, p= 0.016, v= 0.234) between gender and seeking mental health help from parent. Age was found to have a greater influence on mental health seeking behavior in the County as compared with gender.